Dysregulation of Neuregulin-1/ErbB signaling in the hippocampus of rats after administration of doxorubicin - Liao D; Guo Y; Xiang D; Dang R; Xu P; Cai H; Cao L; Jiang P (Dove Medical Press, 2018)
Dehua Liao,1,2 Yujin Guo,3 Daxiong Xiang,2 Ruili Dang,3 Pengfei Xu,3 Hualin Cai,2 Lizhi Cao,1 Pei Jiang3 1Department of Pharmacy, Hunan Cancer Hospital, 2Department of Pharmacy, Institute of Clinical Pharmacy & Pharmacology, Second Xiangya Hospital, Central South University, Changsha, 3Department of Pharmacy, Jining First People’s Hospital, Jining Medical University, Jining, People’s Republic of China Objective: Long-term use of doxorubicin (Dox) can cause neurobiological side effects associated with depression, but the underlying mechanisms remain equivocal. While recent evidence has indicated that Neuregulin-1 (NRG1) and its ErbB receptors play an essential role in neural function, much is still unknown concerning the biological link between the NRG1/ErbB pathway and the Dox-induced neurotoxicity. Therefore, we examined the protein expression of NRG1 and ErbB receptors in the hippocampus of rats following Dox treatment.Materials and methods: The drug was administered every 2 days at a dose of 2.5 mg/kg, and the animals in different groups were treated with intraperitoneal injection for three or seven times, respectively.Results: Our data showed that the rats treated with Dox for seven times (DoxL group) exhibited depression-like behaviors, whereas the short-term treatment (DoxS group) had no effect on the behavioral changes. Dox treatment also induced the neural apoptosis with more severe neurotoxicity. Intriguingly, the expression of NRG1 and the ratio of pErbB4/ErbB4 and pErbB2/ErbB2 were significantly decreased in the DoxL group, but enhanced activation of ErbB receptors was observed in the DoxS group. In parallel, administration of Dox for seven times suppressed the downstream Akt and ERK phosphorylation, while the Akt phosphorylation was enhanced with the administration of Dox for three times.Conclusion: Our data first showed the Dox-induced alterations of the NRG1/ErbB system in the hippocampus, indicating the potential involvement of the NRG1/ErbB pathway in the Dox-induced nervous system dysfunction. Keywords: chemotherapy, neurotoxicity, depression, NRG1/ErbB system, Akt, ERK